Diagnosis of Organic Acidemia - SHAKIBA, Marjan (Iranian Journal of Child Neurology, 2012)
Organic acid occur as physiologic intermediates in variety of intracellular metabolic pathways, such as catabolism of aminoacid, mitochondrial β oxidation of fatty acids, tricarboxilic acid cycle, and cholestrol and fatty acid biosynthesis. The classical organic aciduria represent the pursuit of abnormalities of aminoacid degradation beyond deamination Their diagnostic hallmark is an accumulation of characteristic organic acids.The clinical features result from toxicity of the accumulating methabolites.Treatment involved 1. protein restriction 2. supplementation of aminoacids with unimpaired metabolism as well as trace elements and 3. specific measures for detoxification if indicated. Diagnostic tests consist of CBC, FBS, Bun, Cr, uric organic acid, TG, Cholestrol Ca, P, ALP, VBG, Na, K, Cl, U/A(PH, SG, Ketone), Ammonia, lactate, pyrovate, Ketone body CPK, Aldolase, SGOT, SGPT, BIL, PT, PTT, Plasma aminoacid HPLC, Homocysteine, Urine aminoacid and carbohydrate chromatography, Acyl carnitine profile, urine organic acids and for next steps tissue specimen and enzyme activity and gene study.clinical chemical indices of organid aciduria is Metabolic acidosis, Increased anion gap, Hyperglycemia and hypoglycemia, Ketosis and Ketonuria, Lactic acidosis, Hyperammonemia, Hyperuricemia, Hypertriglyceridemia, increase of transaminase Granulocytopenia, thrombocytopenia and Anemia. Acylcarnitine profile and urine organic acids are two for important tests for differentiation of types oforganic academia.